Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Palapa Alta Utama Kota Depok - Agis Samrotul Fadillah; R.R. Mardiana Yulianti (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The aim of this research is to determine the influence of motivation and work discipline on the performance of employees of PT Palapa Alta Utama Depok City. The method used partially and simultaneously is quantitative. The population and sample in this study were 84 respondents. Data analysis techniques, classical assumption tests, regression tests, correlation coefficient tests, coefficient of determination tests, hypothesis tests. The results of the research show that simultaneously the variables of motivation and work discipline have a significant effect on the performance of employees of PT Palapa Alta Utama Depok City with a value of 0.724 while the remainder is (100 – 52.4%= 47.6%) while the partial test shows that motivation has a significant effect on employee performance of PT Palapa Alta Utama Depok City with a calculated t value > t table or (6,355 > 1,663). This is also reinforced by the ρ value < Sig. 0.05 or (0.000 < 0.05). Thus, H0 is rejected and H1 is accepted. Meanwhile, work discipline has a significant effect on the performance of PT Palapa Alta Utama employees, Depok City with a value of t count > t table or (9.338 > 1.663). This is also reinforced by the ρ value < Sig. 0.05 or (0.000 < 0.05). Thus, H0 is rejected and H1 is accepted. So it can be concluded that motivation and work discipline influence employee performance.